New Insights into Neutrophil Extracellular Traps: Mechanisms of Formation and Role in Inflammation - Yang, Hang; Biermann, Mona Helena; Brauner, Jan Markus; Liu, Yi; Zhao, Yi; Herrmann, Martin (Frontiers in Immunology, 2016)
Recent data suggest that NETosis plays a crucial role in the innate immune response and disturbs the homeostasis of the immune system. NETosis is a form of neutrophil-specific cell death characterized by the release of large web-like structures referred to as neutrophil extracellular traps (NETs). NETs are composed of DNA strands associated with histones and decorated with about 20 different proteins including neutrophil elastase (NE), myeloperoxidase (MPO), cathepsin G, proteinase 3 (PR3), high mobility group protein B1 (HMGB1), and LL37. Reportedly, NETosis can be induced by several microbes, and particulate matter including sterile stimuli, via distinct cellular mechanisms. Meanwhile, suicidal NETosis and vital NETosis are controversial. As we enter the second decade of research on NETosis, we have partly understood NETs as double-edged swords of innate immunity. In this review we will discuss the mechanisms of NETosis, its antimicrobial action and role in autoimmune diseases, as well as the relatively new field of NET-associated mitochondrial DNA.